2022
DOI: 10.1038/s41576-022-00546-w
|View full text |Cite
|
Sign up to set email alerts
|

Probing the dynamic RNA structurome and its functions

Abstract: RNA is a key regulator of almost every cellular process, and the structures adopted by RNA molecules are thought to be central to their functions. The recent fast-paced evolution of high-throughput sequencing-based RNA structure mapping methods has enabled the rapid in vivo structural interrogation of entire cellular transcriptomes. Collectively, these studies are shedding new light on the long underestimated complexity of the structural organization of the transcriptome -the RNA structurome. Moreover, recent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
49
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(68 citation statements)
references
References 119 publications
0
49
0
Order By: Relevance
“…While conventional physical methods, such as NMR, X-ray crystallography and cryo-EM have been instrumental in protein structure analysis, their applications in RNA have been more limited, primarily due to RNA’s large size, high flexibility, and strong dependence on physiological environments. , Computational structure modeling based on minimal free energy calculations and phylogenetic analysis of conservation and covariation also suffer from multiple limitations, such as lack of understanding of RNA folding rules and high computational cost. Therefore, direct measurements of RNA structures in cells have been critical for understanding RNA behavior in various biological and pathological processes . A variety of chemical reactions have been developed and exploited that can modify RNA at certain positions (Figure ) depending on nucleotide reactivity, flexibility, or accessibility, which correlate with RNA structural constraints .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While conventional physical methods, such as NMR, X-ray crystallography and cryo-EM have been instrumental in protein structure analysis, their applications in RNA have been more limited, primarily due to RNA’s large size, high flexibility, and strong dependence on physiological environments. , Computational structure modeling based on minimal free energy calculations and phylogenetic analysis of conservation and covariation also suffer from multiple limitations, such as lack of understanding of RNA folding rules and high computational cost. Therefore, direct measurements of RNA structures in cells have been critical for understanding RNA behavior in various biological and pathological processes . A variety of chemical reactions have been developed and exploited that can modify RNA at certain positions (Figure ) depending on nucleotide reactivity, flexibility, or accessibility, which correlate with RNA structural constraints .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, direct measurements of RNA structures in cells have been critical for understanding RNA behavior in various biological and pathological processes. 13 A variety of chemical reactions have been developed and exploited that can modify RNA at certain positions ( Figure 1 ) depending on nucleotide reactivity, flexibility, or accessibility, which correlate with RNA structural constraints. 14 For example, dimethyl sulfate (DMS) selectively alkylates the N1 position of adenine and N3 position of cytosine on unpaired nucleotides 15 and the 2′-OH in flexible regions can be acylated with Selective 2′-Hydroxyl Acylation analyzed by Primer Extension (SHAPE) reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, direct measurements of RNA structures in cells have been critical for understanding RNA behavior in various biological and pathological processes. 13 A variety of chemical reactions have been developed and exploited that can modify RNA at certain positions (Fig. 1) depending on nucleotide reactivity, flexibility, or accessibility, which correlate with RNA structural constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent studies have shown that cellular RNAs are invariably bound to and often modified by proteins. , Yet, how this regulation, as well as other aspects of the cellular environment, affects RNA structural ensembles, and in turn ligandability, is almost completely unknown. Fortunately, new technologies, most notably high-throughput sequencing-based RNA structure mapping methods, are enabling us to begin to characterize the RNA structurome in living cells . These efforts are likely to reveal new insights into the complexity of RNA folding and structural ensembles, improving our chances of identifying structured RNA targets amenable for selective small molecule targeting in vivo , as well as their bioactive RNA conformations .…”
mentioning
confidence: 99%
“…Fortunately, new technologies, most notably high-throughput sequencing-based RNA structure mapping methods, are enabling us to begin to characterize the RNA structurome in living cells. 111 These efforts are likely to reveal new insights into the complexity of RNA folding and structural ensembles, improving our chances of identifying structured RNA targets amenable for selective small molecule targeting in vivo, as well as their bioactive RNA conformations. 111 In tandem, new technologies are also being developed and deployed for the large-scale cataloguing of RNA−protein interactions, 112 as well as a "call-to-arms" for the development of methods capable of reading out RNA modifications, 113 which at present are poorly understood.…”
mentioning
confidence: 99%